Formulasi Sediaan Emulgel Minyak Bunga Cengkeh (Syzygium aromaticum L.,) Sebagai Antiinflamasi - Tsalasani, Nanda; Larasati, Dwi (JOURNAL OF PHARMACEUTICAL (JOP), 2024)
Bacground: The use of natural ingredients has been widely used in the world of health for treatment, one of which is the clove plant (Syzygium aromaticum L.,). The clove plant is a plant from the Myrtaceae family, a dried simplicia which is widely used, for example as a food ingredient and for use in the pharmaceutical sector. Emulgel consists of two phases, namely a large phase of organic molecules that penetrate water in the form of a gel and a small oil phase. The presence of an oil phase in it makes emulgel superior compared to gel preparations. Obhjective: The aim objective this research is to determine the composition of the combined emulsifier, namely Tween 80 and Span 80, to obtain a good emulgel preparation. Method: The method used was experimental with 3 formulas with different emulsifier compositions and the physical properties of the preparations were evaluated. Result: Based on the experimental results, clove flower oil emulsion was obtained with a clear brownish yellow organoleptic form, the pH value of the three formulas met SNI requirements, namely 6.0 - 6.2; Spreadability ranges from 5.67 - 8.95, viscosity meets SNI standards and minimum content > 90%. Conclusion: Based on research, a good clove flower oil emulgel formula was obtained, namely formula III with a pH value of 6.2 ± 0.3, a viscosity of 22,926 CPs and a spreadability of 8.95 ± 0.03. Formula III also shows that it meets the minimum content test requirements as required by the Indonesian Pharmacopoeia Edition VI